The utilization of modern and traditional medicines by rural elderly Malays in Pahang and Kelantan - Ismail, Zabidah; Wan Su, Kamaruzaman; Hassan, Mohd Hashim Mohd (2003)
An earlier NHMS (1996) reported that 2.3% of elderly population utilized traditional medicines. Some traditional medicines contained steroids. Thus, the aim of the study were to determine the health seeking behaviour of elderly Malays living in rural areas To determine the utilization of medicine both modem and traditionals during a 2 weeks recall.To determine the steroid content of traditional medicine samples. Methodology included a cross-sectional study of elderly Malays living in rural areas in Kelantan and Pahang. Results of the study showed that there were 82.3% elderly that took medications irrespective of types of medications out of 619 elderly.The trends of utilization of modern and traditional medicine among elderly Malays in Kelantan were that 59.3°/0 and 40.9% meanwhile in Pahang were 45% and 75% respectively. Thus, the study showed that the utilization of traditional medicines among elderly Malays in Kelantan and Pahang were 42%. However, the utilization of traditional medicines without age consideration was 47%) which was much higher than previous study and similar to those of France and Australia. The present study also found that some traditional medicines utilized by the elderly do contained steroids such as prednisolone and some other unknown steroids (74%).